Electric discharge coating process variation and its wear properties. (8th July 2021) - Arun, Ilangovan; Yuvaraj, C.; Reddy, G. Chandra Sekhar; Balaji, Nara Siva
The present study elaborates and compare about process variation of electrical discharge coating process through powder mixed and powder metallurgy (semi-sintered) electrode that influences mechanical and metallurgical properties of over duplex stainless. Occurrences of surface roughness, poke, splatters and carters are minimal in deposition of pyrolysis carbon while using the powder metallurgical electrode process of deposition than of powder mixed. Coating layer thickness and porosity are greater in powder mixed having a similar decarburising depth that deserves hardness values with an average of 1, 001 HV to 1, 010 HV across its section. Pyrolysis carbon restricts alloying element deposition that reduced frictional coefficient with greater wear rate compared with the powder metallurgical process. The metallurgical characterisation is performed through a scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), phase identification through X-ray powder diffraction (XRD), optical microscope (OM), mechanical testing through Vickers microhardness, and wear testing by pin-on-disc (POD) tribometer.